Genes with epigenetic alterations in human pancreatic islets impact mitochondrial function, insulin secretion, and type 2 diabetes - Rönn, Tina; Ofori, Jones K.; Perfilyev, Alexander; Hamilton, Alexander; Pircs, Karolina; Eichelmann, Fabian; Garcia-Calzon, Sonia; Karagiannopoulos, Alexandros; Stenlund, Hans; Wendt, Anna; Volkov, Petr; Schulze, Matthias B.; et al. (Nature communications, 2023)
Epigenetic dysregulation may influence disease progression. Here we explore whether epigenetic alterations in human pancreatic islets impact insulin secretion and type 2 diabetes (T2D). In islets, 5,584 DNA methylation sites exhibit alterations in T2D cases versus controls and are associated with HbA1c in individuals not diagnosed with T2D. T2D-associated methylation changes are found in enhancers and regions bound by β-cell-specific transcription factors and associated with reduced expression of e.g. CABLES1 , FOXP1 , GABRA2 , GLR1A , RHOT1 , and TBC1D4 . We find RHOT1 (MIRO1) to be a key regulator of insulin secretion in human islets. Rhot1 -deficiency in β-cells leads to reduced insulin secretion, ATP/ADP ratio, mitochondrial mass, Ca 2+ , and respiration. Regulators of mitochondrial dynamics and metabolites, including L-proline, glycine, GABA, and carnitines, are altered in Rhot1 -deficient β-cells. Islets from diabetic GK rats present Rhot1-deficiency. Finally, RHOT1 methylation in blood is associated with future T2D. Together, individuals with T2D exhibit epigenetic alterations linked to mitochondrial dysfunction in pancreatic islets. Type 2 diabetes (T2D) is characterized by hyperglycemia caused by insufficient insulin release from pancreatic islets, often in combination with insulin resistance. Here the authors present an epigenetic case-control study in human pancreatic islets revealing changes that contribute to type 2 diabetes development, e.g., epigenetic downregulation of RHOT1.